2005
DOI: 10.1111/j.1468-2982.2005.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Amitriptyline and Flunarizine on Weight Gain and Serum Leptin, C Peptide and Insulin Levels when used as Migraine Preventive Treatment

Abstract: The tricyclic antidepressant amitriptyline (AMT) and the calcium channel blocker flunarizine are frequently used in the preventive treatment of migraine, but the side-effect of prominent weight gain that frequently emerges during preventive treatment of migraine with these agents often leads to the discontinuation of therapy. In this study, we aimed to investigate the possible relationship between the weight gain associated with the use of these agents and serum levels of leptin, C-peptide and insulin in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
(65 reference statements)
0
35
0
3
Order By: Relevance
“…Review of references in these manuscripts and related‐reviews identified 2 additional studies . Of these 21 manuscripts, 6 were reviews, 3 were non‐adipokine studies, and 1 utilized an animal model of aura and were thus excluded, leaving 12 studies which evaluated blood levels of leptin in those with migraine . Of these 11 manuscripts, 6 included crude interictal leptin evaluations in those with migraine as compared to controls and 5 evaluated leptin levels before and after abortive or preventive therapy in those with migraine.…”
Section: Resultsmentioning
confidence: 99%
“…Review of references in these manuscripts and related‐reviews identified 2 additional studies . Of these 21 manuscripts, 6 were reviews, 3 were non‐adipokine studies, and 1 utilized an animal model of aura and were thus excluded, leaving 12 studies which evaluated blood levels of leptin in those with migraine . Of these 11 manuscripts, 6 included crude interictal leptin evaluations in those with migraine as compared to controls and 5 evaluated leptin levels before and after abortive or preventive therapy in those with migraine.…”
Section: Resultsmentioning
confidence: 99%
“…42 A second study which evaluated serum leptin levels in migraineurs before and after preventive treatment (tx) with amitriptyline reported increased leptin levels after treatment (pre-tx: 7.15 ± 1.12; post-tx: 16.85 ± 2.38, P < .01). 43 However, one small case series of 6 migraine patients reported that leptin was decreased by 39.2 ± 6.5% from baseline following 20 weeks of treatment ( P = .013). 44 Most recently Bernecker et al evaluated fasting leptin levels in 40 non-obese female migraineurs.…”
Section: Central Regulation Of Feeding and Its Overlap With Migraine mentioning
confidence: 96%
“…Leptin levels of migraine patients, however, have not yet been explored fully. Berilgen et al 14 found elevated leptin levels in migraine patients in the third month of preventive treatment with amitriptyline and flunarizine when compared with baseline levels, probably as a physiological response to counterbalance the weight gain. In this study, we aimed to assess leptin levels in a headache‐free period of migraine patients who did not use any medication interfering in leptin levels, and investigate the relation to vascular risk factors.…”
mentioning
confidence: 98%